The study of chemical modifications on the properties of soy protein isolate (SPI) / kapok husk (KH) biocomposite films for agriculture applications - Ramyah Kalai Chelvie, Pani Sellivam (Universiti Malaysia Perlis (UniMAP), 2018)
Doctor of Philosophy in Materials Engineering